Association of size for gestational age and dehydroepiandrosterone sulfate with cardiometabolic risk in central precocious puberty girls - Zhang, Guijiao; Yu, Huan; Yu, Shengxu; Luo, Xiaoping; Liang, Yan; Hou, Ling; Wu, Wei (Frontiers in Endocrinology, 2023)
Objective: To assess whether size for gestational age and dehydroepiandrosterone sulfate (DHEAS) are associated with cardiometabolic risk in central precocious puberty (CPP) girls. Methods: The retrospective study included 443 patients with newly diagnosed CPP. Subjects were categorized by birth weight for gestational age (appropriate [AGA], small [SGA], and large [LGA] for gestational age) and serum DHEAS concentration (high [≥75th percentile] and normal [<75th percentile] DHEAS). Cardiometabolic parameters were examined. Composite cardiometabolic risk (CMR) score was calculated based on BMI, blood pressure, glucose, insulin, triglyceride, and HDL cholesterol. Non-obesity CMR score was computed, omitting the value from BMI. Logistic regression models, general linear models, and partial correlation analyses were used to evaluate associations. Propensity score matching was performed for sensitivity analyses. Results: Overall, 309 patients (69.8%) were born AGA, 80 (18.1%) were born SGA, and 54 (12.2%) were born LGA. Compared with AGA counterparts, CPP girls born SGA was more prone to have elevated HbA1c (adjusted OR=4.54; 95% CI, 1.43-14.42) and low HDL cholesterol (adjusted OR=2.33; 95% CI, 1.18-4.61). On the contrary, being born LGA was not associated with increased risk for any glucose or lipid derangements. Despite elevated CMR score was more common among individuals born LGA than AGA (adjusted OR=1.84; 95% CI, 1.07-4.35), no substantially difference was found on non-obesity CMR score (adjusted OR=0.75; 95% CI, 0.30-1.88). When controlling for age, birth weight SDS and current BMI-SDS, individuals with high DHEAS exhibited higher HDL cholesterol and apolipoprotein A-1 concentrations and lower triglyceride level and non-obesity CMR score. Furthermore, DHEAS correlated positively with HDL cholesterol and apolipoprotein A-1 and negatively with triglyceride, prominently in girls born SGA, after adjustments for the three abovementioned confounders. Sensitivity analyses corroborated the findings. Conclusion: Among CPP girls, those born SGA was more likely to possess cardiometabolic risk factors compared to their AGA peers. The difference we observed in cardiometabolic risk between individuals born LGA and AGA was driven by BMI. High DHEAS was associated with favorable lipid profile in CPP girls, even in subjects born SGA.